Oman 1974 - 2022/23 - Axon, Anthony,; Hewitt, Susan, (Contemporary Archive of the Islamic World ;, 2025)
The seventh in the CAIW series, this title draws on the 50 years of experience of Cambridge based World of Information. During most of the period covered, Oman was ruled by Sultan Qaboos bin Said, overcoming several handicaps, including modest hydrocarbon revenues, and during the first years of Qaboos' reign, a rebellion in the southern province of Dhofar. The latter was often described as a full-blown war with the neighbouring People's Democratic Republic of the Yemen (PDRY) and its Soviet supporters. Nevertheless, this strategically located, mostly Ibadhi sect Sultanate, has developed from a medieval, into a modern state.